Finding the gaps in managing Fabry disease in women: the Romanian experience. (3rd October 2022) - Mursa, A; Militaru, S; Neculae, G; Adam, R; Radoi, V; Rusu, E; Popescu, B A; Jurcut, R
Abstract: Introduction: Fabry disease (FD) is an X-linked rare lysosomal storage disease caused by mutations in the GLA gene which lead to decrease in α Gal A enzyme activity and tissue accumulation of lysosomal globotriaosylceramide (Gb3) and globotriaosylsphingosine (lyso-Gb3). Due to X linked transmission, males are hemizygous, and females are heterozygous and were initially thought to be unaffected. However, women with FD can vary from asymptomatic, mildly symptomatic, to severely symptomatic as males. The aim of this study is to evaluate the particularities of FD presentation, cardiac imaging and management in females from the full Romanian FD cohort as compared to male patients. Methods: This study included all consecutive patients diagnosed in or referred to our center with FD between 2014–2021. All patients had a complete clinical, biological and cardiac imaging workup. Results: During the inclusion interval, data from 66 consecutive Romanian FD patients (37 women and 29 men) from 29 unrelated families were collected. Diagnosing mode in FD women differs compared to men (p<0.001): most women were diagnosed through family screening or by a cardiologist, while most men were diagnosed by nephrologists. Women had higher levels of α Gal A levels (1.3±0.8 μmol/L/h vs 0.5±0.7 μmol/L/h, normal cutoff >1.2) (p<0.001) and smaller levels of lyso-GB3 (5.8±2.6 ng/ml vs 110±35.6 ng/ml, normal cutoff<3.8) (p<0.001). More women are asymptomatic carriers than men (27% vs 3.4%), but when symptoms were present, they could be as severe as in men. Enrolled women were older (50.9±16.3 vs 41±14.9 years, p=0.014), diagnosed later (46.8±16.8 vs 32.7±14.3 years, p<0.001) and had later symptom onset of the disease compared with men (38.1±14.4 vs 20.3±14.9 years, p<0.001). Women had less angiokeratomas (p=0.001) and hypohydrosis (p=0.04), with no difference in cornea verticillata or ENT involvement. Both women and men developed cardiac symptoms starting from the fifth decade, with no differences in terms of angina, NYHA class, syncope between sexes. Women tend to have a lower prevalence of LVH compared to men (p=0.052), with no differences regarding ejection fraction or global longitudinal strain between genders. Regarding other organs involved, women were equally affected as men from acroparesthesia and stroke, with similar age at first cerebrovascular event. Women had milder kidney involvement (stages 1 and 2) when compared to men (56.8% vs 37.9%, p=0.004). Regardless of these findings, it appeared that women were less treated with pathogenic therapy comparing to men (48.6% vs 82.7%) (p=0.004). Conclusions: Women with FD are not merely genetic carriers as they can be as affected as men. However, they benefit later from diagnosis and less of pathogenic therapy. Further studies with more female participations are needed to better understand the Fabry burden and needs in women. Funding Acknowledgement: Type of funding sources: None.